2016
DOI: 10.1103/physrevd.93.055030
|View full text |Cite
|
Sign up to set email alerts
|

Higgs boson spectra in supersymmetric left-right models

Abstract: We present a comprehensive analysis of the Higgs boson spectra in several versions of the supersymmetric left-right model based on the gauge symmetryA variety of symmetry breaking sectors are studied, with a focus on the constraints placed on model parameters by the lightest neutral CP even Higgs boson mass M h . The breaking of SU (2) R symmetry is achieved by Higgs fields transforming either as triplets or doublets, and the electroweak symmetry breaking is triggered by either bidoublets or doublets. The Higg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…Unlike in non-supersymmetric left-right symmetric extensions of the SM, predictions for the masses of the right-handed gauge bosons exhibit an upper limit, which depends on the SUSY breaking scale [62,63], as the charge-conserving vacuum is not stable when v R M SUSY . However, such a limit does not hold if B−L = 0 triplets stabilize the vacuum and the right-handed gauge sector is extremely heavy, with masses of O(10 11 ) GeV [54][55][56].…”
Section: Right-handed Gauge Sectormentioning
confidence: 94%
See 1 more Smart Citation
“…Unlike in non-supersymmetric left-right symmetric extensions of the SM, predictions for the masses of the right-handed gauge bosons exhibit an upper limit, which depends on the SUSY breaking scale [62,63], as the charge-conserving vacuum is not stable when v R M SUSY . However, such a limit does not hold if B−L = 0 triplets stabilize the vacuum and the right-handed gauge sector is extremely heavy, with masses of O(10 11 ) GeV [54][55][56].…”
Section: Right-handed Gauge Sectormentioning
confidence: 94%
“…If the slepton masses are much smaller than v R , the correction will be negative and worsen the problem of the negative mass eigenvalue [63]. The large value of v R that we have adopted hence disfavors a light slepton option.…”
Section: Jhep05(2017)015mentioning
confidence: 98%
“…If the slepton masses are much smaller than v R , the correction will be negative and worsen the problem of the negative mass eigenvalue [21]. Recently it was found that the gauge and Higgs sectors can also significantly contribute to the doubly charged Higgs mass, which opens up a window for lighter right sleptons and sneutrinos [22].…”
Section: Gauge Extension Susylrmentioning
confidence: 99%
“…A variety of LRSUSY models have been discussed in literature with different scalar sectors for the symmetry breaking mechanism [7,8]. The one we consider here is the minimal LRSUSY model with automatic R-partiy conservation [9] where the right-handed symmetry is broken by scalar triplets fields as they acquire non-zero vacuum expectation values (VEVs).…”
Section: Introductionmentioning
confidence: 99%